New U-Pb zircon data for Maarianvaara granite and Tohmajärvi volcanic complex, eastern Finland: geologic implications - Asko Kontinen; Jarmo Kohonen; Perttu Mikkola; Matti Kurhila (Bulletin of the Geological Society of Finland)
New U-Pb zircon ages reported for samples from the Maarianvaara granite and Tohmajärvi volcanic complex (TVC) corroborate previous estimates of their magmatic emplacement at ca. 1.85 Ga and 2.11 Ga, respectively. The ca. 1.85 Ga age of the largely undeformed Maarianvaara granite, which cuts the Proterozoic protomylonitic foliation in the Archean basement gneisses, sets a minimum age for the basement-involved thrusting in North Karelia. Geological evidence and geochemical data for the Kylmäkallio sill, dated at ca. 2.11 Ga from Tohmajärvi, indicate it is cogenetic/coeval with mafic metavolcanic/hypabyssal intercalations occurring in both the TVC and the surrounding black schist layered metasedimentary rocks of the Tohmajärvi suite. Thus, burial of organic carbon in the sedimentary protoliths of the Tohmajärvi succession was evidently occurring at ca. 2.11 Ga, about 50 Ma earlier than has been assumed in some recent time-stratigraphic interpretations.